Effects of resistance training on running economy: a systematic review and meta-analysis - Arthur Zecchin; Leonardo R C de Lima; Enrico F Puggina; Márcio Fernando Tasinafo-Júnior (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Running economy (RE) is a key determinant of endurance performance in long-distance runners, influencing their efficiency and energy expenditure. Resistance training has been proposed as a strategy to enhance RE, yet its effectiveness remains debated.